Der integrale mehrdimensionale Grenzwertsatz für die Konvergenz gegen das stabile Grenzgesetz - Banys, J. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. И. Банис. Об интегральной предельной теореме при сходимости к устойчивому закону в многомерном случае J. Banys. Daugiamatė integralinė teorema stabilaus ribinio dėsnio atveju